2004
DOI: 10.1186/1471-2199-5-1
|View full text |Cite
|
Sign up to set email alerts
|

Translation of the radioresistance kinase TLK1B is induced by γ-irradiation through activation of mTOR and phosphorylation of 4E-BP1

Abstract: Background: The mammalian protein kinase TLK1 is a homologue of Tousled, a gene involved in flower development in Arabidopsis thaliana. The function of TLK1 is not well known, although knockout of the gene in Drosophila, or expression of a dominant negative mutant in mouse cells causes loss of nuclear divisions and chromosome missegregation probably due to alterations in chromatin remodeling capacity. Overexpression of TLK1B, a spliced variant of the TLK1 mRNA, in a model mouse cell line increases their resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(26 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…3E). Akt has been shown to activate mTOR, which plays an important role in protein synthesis (33). We next examined a role of mTOR in CO-induced phosphorylation of p70 S6K and eIF-4E.…”
Section: Co-induced Increases In Hif-1␣ and Vegf Expression Arementioning
confidence: 99%
“…3E). Akt has been shown to activate mTOR, which plays an important role in protein synthesis (33). We next examined a role of mTOR in CO-induced phosphorylation of p70 S6K and eIF-4E.…”
Section: Co-induced Increases In Hif-1␣ and Vegf Expression Arementioning
confidence: 99%
“…If for example TLK1/1B is the main H3 kinase involved in a “chromosomal response” to DNA damage, then ATM-mediated inhibition of TLK1 (see below) is expected to result in a loss of H3 phosphorylation by endogenous phosphatases and in altered kinetics of chromatin assembly during replication and/or repair. It is possible that physiologically the increased TLK1B synthesis following IR [56] can help offset the loss of TLK activity resulting from IR and restore appropriate levels of H3P later on during the recovery. The reduction of H3P following genotoxic stress (IR) was previously reported also by another group [57].…”
Section: General Information On Tousled-like Kinasesmentioning
confidence: 99%
“…Instead, we have independently cloned the TLK1B splice variant with a completely different screen, based upon polysomal redistribution of weakly translated transcripts that become preferentially recruited upon overexpression of eIF4E [8]. We subsequently found that TLK1B is synthesized efficiently in several cell lines overexpressing the translation factor/oncogene eIF4E, and we then presented several lines of evidence to confirm its translational regulation, particularly after genotoxic stress [56]. The significance of this translational regulation is discussed later when I emphasize the role of TLKs in DNA repair and protection from genotoxic agents, including IR and UV.…”
Section: Tlks In Man As Guardians Of Genome Stability and Their mentioning
confidence: 99%
“…Briefly, Rh30 or Rh1 cells grown in 100-mm dishes in serum-free DMEM medium were pretreated with or without rapamycin (100 ng/ml) in the presence or absence of IGF-1 (10 ng/ml) for 24 h. Subsequently, the cells were washed with PBS twice, switched to 3 ml of Met/Cys-free DMEM (Mediatech) containing 10 M MG-132 (Calbiochem), a proteasome inhibitor (to prevent protein from degradation), and then pulsed with 0.3 mCi/ml [ 35 S]Met/Cys (MP Biomedicals, Solon, OH) for up to 4 h in the presence or absence of rapamycin (100 ng/ml) and IGF-1 (10 ng/ml), as described previously (36). Subsequently, the labeled cells were lysed in 50 mM Tris, pH 7.2, containing 150 mM NaCl, 1% sodium deoxycholate, 0.1% SDS, 1%Triton X-100, 10 mM NaF, 1 mM Na 3 VO 4 , and protease inhibitor mixture (1:1000, Sigma).…”
Section: Methodsmentioning
confidence: 99%